Study on Impact of Turbine Location on Hydrodynamics in Tidal Farm - Hongqiang Zhang; Daming Li; Yanqing Li; Ting Yang; Shan Luo; Shunfa Tian; Shilong Bu (Discrete Dynamics in Nature and Society)
This work aims at investigating the impact of different tidal turbine locations on hydrodynamics in near-field and far-field flow; thus, three- and two-dimensional (3- & 2-D) models were exploited in combination and applied in a case study of Putuo-Hulu Islands’ tidal farm. We present a method for the simplification of tidal turbine which, based on the energy equation, determines turbine’s equivalent roughness by calculating resistance loss in flow passage. A 3-D turbine model of near-field flow in the frame of Computational Fluid Dynamics was constructed, and the flow velocity distributions in 7 combinations of “impeller rotating speed - inflow velocity” were simulated. Also a 2-D tidal model of far-field flow was established, and Finite Element Method was adopted to solve the 2-D shallow water circulation equations; thus, the impact of tidal turbine could be simulated by utilizing different location’s compositive roughness. The results show that the impact of turbine location on hydrodynamics is depending on the open degree of sea area, channel trend, and bathymetric and geographic features and that the farther distance from the turbine, the less impact on the flow field. Overall, the impact of turbine location on far-field flow is not significant, and the flow velocity varies below 8% relative to the velocity prior to turbine installation.